Whether you're a student or a professional, IDNLearn.com has answers for everyone. Find the information you need quickly and easily with our reliable and thorough Q&A platform.
Sagot :
To determine \(\cos(\theta)\) given that \(\sin(\theta) = -\frac{1}{3}\) and \(\pi < \theta < \frac{3\pi}{2}\), follow these steps:
1. Identify the Quadrant:
Since \(\pi < \theta < \frac{3\pi}{2}\), the angle \(\theta\) is in the third quadrant. In the third quadrant, sine is negative and cosine is also negative.
2. Use the Pythagorean Identity:
The Pythagorean identity states:
[tex]\[ \sin^2(\theta) + \cos^2(\theta) = 1 \][/tex]
3. Substitute the Known Sine Value:
Given \(\sin(\theta) = -\frac{1}{3}\), first find \(\sin^2(\theta)\):
[tex]\[ \sin^2(\theta) = \left(-\frac{1}{3}\right)^2 = \frac{1}{9} \][/tex]
4. Express \(\cos^2(\theta)\) in Terms of Known Values:
We use the identity \(\sin^2(\theta) + \cos^2(\theta) = 1\) to solve for \(\cos^2(\theta)\):
[tex]\[ \cos^2(\theta) = 1 - \sin^2(\theta) \][/tex]
Substituting \(\sin^2(\theta)\):
[tex]\[ \cos^2(\theta) = 1 - \frac{1}{9} \][/tex]
Simplify the expression:
[tex]\[ \cos^2(\theta) = \frac{9}{9} - \frac{1}{9} = \frac{8}{9} \][/tex]
5. Determine \(\cos(\theta)\):
To find \(\cos(\theta)\), take the square root of both sides. Since \(\cos(\theta)\) is in the third quadrant and must be negative:
[tex]\[ \cos(\theta) = -\sqrt{\frac{8}{9}} = -\frac{\sqrt{8}}{3} = -\frac{2\sqrt{2}}{3} \][/tex]
Therefore, the value of \(\cos(\theta)\) is:
[tex]\[ \boxed{-\frac{2\sqrt{2}}{3}} \][/tex]
1. Identify the Quadrant:
Since \(\pi < \theta < \frac{3\pi}{2}\), the angle \(\theta\) is in the third quadrant. In the third quadrant, sine is negative and cosine is also negative.
2. Use the Pythagorean Identity:
The Pythagorean identity states:
[tex]\[ \sin^2(\theta) + \cos^2(\theta) = 1 \][/tex]
3. Substitute the Known Sine Value:
Given \(\sin(\theta) = -\frac{1}{3}\), first find \(\sin^2(\theta)\):
[tex]\[ \sin^2(\theta) = \left(-\frac{1}{3}\right)^2 = \frac{1}{9} \][/tex]
4. Express \(\cos^2(\theta)\) in Terms of Known Values:
We use the identity \(\sin^2(\theta) + \cos^2(\theta) = 1\) to solve for \(\cos^2(\theta)\):
[tex]\[ \cos^2(\theta) = 1 - \sin^2(\theta) \][/tex]
Substituting \(\sin^2(\theta)\):
[tex]\[ \cos^2(\theta) = 1 - \frac{1}{9} \][/tex]
Simplify the expression:
[tex]\[ \cos^2(\theta) = \frac{9}{9} - \frac{1}{9} = \frac{8}{9} \][/tex]
5. Determine \(\cos(\theta)\):
To find \(\cos(\theta)\), take the square root of both sides. Since \(\cos(\theta)\) is in the third quadrant and must be negative:
[tex]\[ \cos(\theta) = -\sqrt{\frac{8}{9}} = -\frac{\sqrt{8}}{3} = -\frac{2\sqrt{2}}{3} \][/tex]
Therefore, the value of \(\cos(\theta)\) is:
[tex]\[ \boxed{-\frac{2\sqrt{2}}{3}} \][/tex]
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Thank you for trusting IDNLearn.com. We’re dedicated to providing accurate answers, so visit us again for more solutions.